The hidden crisis: double burden of malnutrition among refugee children in South Asia – a systematic review and meta-analysis from observational studies - Panchal, Pooja; Usman, Mohd; Longkumer, Tajung; Babu, Reshma Susan; Khatib, Mahalaqua Nazil; Razak, Shariza Abdul; Menon, Kavitha (Frontiers in Nutrition, 2025)
Background Children living in refugee camps in South Asian countries suffer from undernutrition. However, the emerging prevalence of double burden of malnutrition could potentially cause a crisis in the healthcare of the refugee population. Double burden increases the risk for co-morbidities, poor functional health, and increased risk for premature death among these children. The study aims to assess the prevalence of malnutrition among refugee children in South Asia. Methods This systematic review and meta-analysis followed the standard Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines using CoCoPop mnemonic approach. We searched JSTOR, Scopus, PubMed, Web of Science, and MEDLINE databases for studies on the prevalence of malnutrition in refugee children from 1984 to August 2024 with restricted English language. The screening of research articles was undertaken using COVIDENCE 2.0 software. The JBI checklist was used to assess the methodological quality of the included articles. The meta analysis was carried out using MedCalc 22.018 software. The gray literature was manually searched from the reputed organizations focusing on refugee children and was narratively analyzed for malnutrition statistics. Furthermore, the corroboration of primary research articles and gray literature was conducted for comprehensive understanding. Results The review included 10 full-text research articles, all with cross-sectional study design and 11 gray literatures. The 10 studies covered a total of 4,274 participants with 3,536 urban and 738 rural refugee children aged between 0 and 19 years [refugee children (n = 8) and refugee adolescents (n = 2)]. The sample size of the included studies varied between 58 and 1,087 and mostly from Bangladesh. The prevalence of stunting ranged from 3.9–75.4% in the included studies [pooled prevalence: 31.8% (95% CI: 18.6–46.6%)]; wasting between 0.3–24.3% [pooled prevalence:10.1% (95% CI: 4.6–17.3)]; underweight between 4.4–65% [pooled prevalence: 19.1% (95% CI: 10.8–29.2%)]; and overweight between 3 and 24% [pooled prevalence: 6.5% (95% CI: 2.6–12.1%)]. Time trend analysis of the prevalence of malnutrition showed a decreasing trend in underweight, an increasing trend for stunting and wasting, and overweight including a rising prevalence of dual burden of under-and overnutrition. Discussion The study indicates a high prevalence of undernutrition and a rising prevalence of overnutrition -the Asian paradox of the double burden of malnutrition in refugee children living in South Asia. The coexisting double burden of malnutrition among refugee children calls for comprehensive programs and policies for the prevention and management of the double burden of malnutrition.